Spanish Renaissance High Culture in Soviet Historiography: Interdisciplinary Aspect - Zaitsev, Alexander A.; Antonova, Natalia V. (Journal of History Culture and Art Research, 2017)
The tradition of studying Spanish Renaissance in Russia is quite a complicated phenomenon, which requires a detailed analysis. The main questions which arise when referring to the issue are those of developmental patterns and interdisciplinary aspect of the letter. Spanish Renaissance culture is traditionally the subject to scrutiny for historians, philologists and art historians. The present article aims to outline a preliminary picture of interdisciplinary interaction, which gained momentum in the Soviet period of Russian Hispanism. Special attention is paid to the imminent figures of Spanish Renaissance historiography, as well as their ideas and concepts. The evolution of Spanish Renaissance studies is described against the background of the principal research areas. The present paper will be of interest to both intellectual historians and scholars investigating Renaissance and medieval history.